PELATIHAN PEMBUATAN LAPORAN KEUANGAN SEDERHANA BERBASIS APLIKASI SI APIK PADA UMKM BOLU RASA BAKERY BEKASI - Yusbardini Yusbardini; Daryyl Daryyl; Nicholas Nicholas (PROSIDING SERINA, 2021)
Micro, Small and Medium Enterprises (MSMEs) face obstacles in preparing standardized financial reporting, not knowinghow much pure profit they will get, lack of understanding of basic knowledge of financial records, lack of understanding of Android-based financial application knowledge, and difficulty getting financing from financial institutions. The purpose ofthis community service is to increase understaKURnding of basic knowledge of financial records and improve the ability to operate Android-based financial applications through education and training on Android-based financial bookkeeping.Community service involves the perpetrators of SMEs Bolu Rasa Bakery in Pejuang Village, Bekasi as the object of research. The method used in the training isthe online method, indirect faceto-face &mentoring, namely by analyzing andproblem solving. Financial bookkeeping materials are presented with lectures, training, questions and answers, demonstrations, and online case resolution. The material is made in a simple and attractive way so that the financial bookkeeping material is easy to understand for SMEs in Bolu Rasa Bakery. Furthermore, the recording process begins withexamples of simple transactions that are usually carried out through the SI APIK application, an android application issuedby Bank Indonesia. The results of financial literacy training and financial reporting assistance through this android-basedapplication are expected to run well, as well as an increase in understanding of basic knowledge of financial records and an increase in understanding of the operation of android-based financial applications.